Collagenolytic Activity Is Associated with Scar Resolution in Zebrafish Hearts after Cryoinjury - Laurent Gamba; Armaan Amin-Javaheri; Jieun Kim; David Warburton; Ching-Ling Lien (Journal of Cardiovascular Development and Disease, 2017)
Myocardial infarction is the major cause of cardiac injury in western countries and can result in a massive loss of heart cells, leading eventually to heart failure. A fibrotic collagen-rich scar may prevent ventricular wall rupture, but also may result in heart failure because of its stiffness. In zebrafish, cardiac cryoinjury triggers a fibrotic response and scarring. Unlike with mammals, zebrafish heart has the striking ability to regenerate and to resolve the scar. Thus, understanding the mechanisms of scar resolution in zebrafish heart might facilitate the design of new therapeutic approaches to improve the recovery of patients. To visualize the collagenolytic activity within the zebrafish heart following cryoinjury, we used an in situ collagen zymography assay. We detected expression of mmp2 and mmp14a and these matrix metalloproteinases might contribute to the collagenase activity. Collagenolytic activity was present in the wound area, but decreased as the myocardium regenerated. Comparison with neonatal mouse hearts that failed to regenerate after transmural cryoinjury revealed a similar collagenolytic activity in the scar. These findings suggest that collagenolytic activity may be key to how the zebrafish heart resolves its scar; however, it is not sufficient in mouse hearts that lack efficient myocardial regeneration.